Tricuspid Valve Replacement in a Patient with a Leadless Cardiac Pacemaker: Current Guidelines and Recommendations for Perioperative Management. (1st July 2021) - Hames, River; Hayanga, J. W. Awori; Schmidt-Krings, Diane; Goldhardt, Timothy; Bozek, John; Siddoway, Donald; Schmidt, Stanley; Lobban, John; Hayanga, Heather K.
Abstract : Leadless cardiac pacemakers were developed to reduce complications associated with conventional transvenous pacemakers. While this technology is still relatively new, devices are increasingly being implanted. The perioperative management of patients with these devices has been underreported; we thus seek to add to the limited body of knowledge of perioperative management of patients with leadless cardiac pacemakers. An elderly female patient with a Micra VR transcatheter pacing system leadless cardiac pacemaker placed for tachycardia-bradycardia syndrome with intermittent complete heart block was scheduled for elective tricuspid valve replacement for severe tricuspid regurgitation. Pacemaker interrogation was performed several hours prior to the scheduled surgery based on the electrophysiologist's availability; the device was kept in its programmed VVIR mode, and the base rate was increased from 60 to 80 beats per minute in anticipation of the upcoming surgery. Upon preoperative evaluation, the anesthesiologist asked that the electrophysiology team be placed on standby intraoperatively due to the concern that either oversensing in the setting of pacemaker dependence and/or undesirable tachycardia from rate-responsive pacing could occur. The surgeon used monopolar electrocautery for the duration of the cardiac surgery. Despite the patient having evidence of pacemaker dependence in the intensive care unit preoperatively, no electromagnetic interference leading to oversensing nor rate modulation was detected during intraoperative electrocardiographic and intraarterial invasive monitoring. Evidence-based guidelines regarding perioperative management specifically of leadless cardiac pacemakers do not exist. As these devices become more prevalent, further evaluation will be paramount to determine whether existing guidelines for perioperative management of conventional transvenous pacemakers apply.